Les Franque et les bâtiments hospitaliers d’Avignon au XVIIIe siècle : entre tradition et mutations - Béatrice Gaillard (In Situ)
The residence at Avignon of the Holy See, during the fourteenth century, led to the creation of numerous hospital establishments, the first duty of which was to take care of pilgrims. With the departure of the papacy, these establishments were abandoned, in certain cases, or re-used. By the eighteenth century, the city had the same population as it had had during papal times, and medieval hospital buildings such as Sainte-Marthe and Saint-Bénézet were modernised and enlarged. They were establishments which were supposed to specialise in certain illnesses and certain social problems of their time. The Avignon architects, in particular Jean-Baptiste Franque and his two sons François II and Jean-Pierre, were often called upon to improve the hospital buildings and the comfort they offered, to a point where they seemed to occupy official positions as hospital architects. The analysis of their work gives a better understanding of the importance of the hospital tradition in the city of Avignon, and to see how architecture was gradually adapted to more modern visions of medical treatment and nursing.